Estudo longitudinal dos determinantes, desfechos e transição dos estados e componentes do fenótipo de fragilidade entre idosos da comunidade - PEGORARI, Maycon Sousa (2018)
The objective of this study was to analyze the determinants, outcomes and transition of frailty phenotype (FF) states and components among community-dwelling elderly followed up for 24 months. Longitudinal study was performed with a cohort with two waves, one at the baseline (2014 - n = 510) and the other at 24 months (2016 - n = 353) conducted with elderly people in the urban area of Uberaba - MG. A structured instrument was used referring to socioeconomic data and health indicators; Mini Mental State Examination (MMSE), Katz and Lawton and Brody Scales; Short Physical Performance Battery (SPPB), Falls Efficacy Scale-International (FES-I) Brazil and FF. Descriptive and inferential statistical analysis were performed with the chi-square, McNemar, t-student, t-paired and ANOVA one-way tests and binary, multinomial and multivariate Cox logistic regression models (p <0.05); and KaplanMeier survival analyzes using the Statistical Package for Social Sciences (SPSS), version 21.0. Project approved by the Ethics Committee, reports nº 493.211 and nº 573.833. There was an increase in frailty (13%) and a decrease in non-frail elderly (30.9%) during follow-up, although there were no significant differences. With the exception of the low level of physical activity, the other FF components showed a decrease, although the percentage values remained close in the comparison. Among the frail elderly, 34% remained in this condition, while 30% returned to pre-frail. Prefrail elderly remained in this state (55.9%), 24.2% moved to the non-frail category and 12% became frail. The majority of the non-frail became pre-frail (51.9%) and no individual moved to frailty. The highest percentage of elderly people who died were frail (32%), followed by pre-frail (7.1%) and non-frail (4.7%). The age group 80 years and older set the predictor for the conditions of pre-frailty and frailty; while the dependence on the basic activities of daily living (BADL) and the low physical performance of lower limbs (LLL) for frailty. The increase in one unit of the advanced activities of daily living score decreased by 15% the occurrence of frailty. The predictor factors associated with FF components were consolidated: self-report of exhaustion and / or fatigue (lack of income and poor and low physical activity of lower9 limbs), decreased muscle strength (BADL dependence and low physical performance of lower limbs), slow gait speed (very bad and low physical performance of lower limbs) and low physical activity level (age range of 75 years and over and dependence on instrumental activities of daily living). The conditions of frailty and pre-frailty were risk of falls, while the frailty to death. The FF components represented predictors for falls (except for self-report of exhaustion and / or fatigue and decrease of muscle strength) and for mortality (except unintentional weight loss and decreased muscle strength); and the low level of physical activity for hospitalization. The results of this investigation provided information on the occurrence of transition between the states of frailty, determining factors and the predictive capacity of this syndrome and components for adverse health outcomes among the elderly in the two year period.